2021
DOI: 10.1017/s0007485321000614
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of organophosphorus insecticide phoxim on patch time allocation and oviposition behavior in a parasitoid wasp Meteorus pulchricornis

Abstract: Parasitoid wasps are key agents for controlling insect pests in integrated pest management programs. Although many studies have revealed that the behavior of parasitic wasps can be influenced by insecticides, the strategies of patch time allocation and oviposition have received less attention. In the present study, we forced the endoparasitoid Meteorus pulchricornis to phoxim exposure at the LC30 and tested the foraging behavior within patches with different densities of the host, the larvae of the tobacco cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…pulchricornis, implying a potential impact of insecticides on the olfactory recognition of M. pulchricornis . However, the interaction between insecticides and OBPs has not been explored in M.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pulchricornis, implying a potential impact of insecticides on the olfactory recognition of M. pulchricornis . However, the interaction between insecticides and OBPs has not been explored in M.…”
Section: Introductionmentioning
confidence: 99%
“…21 In the previous study, we found that the occurrence of phoxim exposure harmed the foraging and oviposition behaviors and exhibited a decrease in the number of host visits in M. pulchricornis, implying a potential impact of insecticides on the olfactory recognition of M. pulchricornis. 26 However, the interaction between insecticides and OBPs has not been explored in M. pulchricornis so far; whether MpulOBPs can bind to the insecticides remains to be elucidated. In this study, we further investigated the binding affinities of MpulOBP6 and found that the binding mechanism of MpulOBP6 to three insecticides (phoxim, chlorpyrifos, and chlorfenapyr) and several important amino acid residues were determined that play a crucial role in their binding processes.…”
Section: ■ Introductionmentioning
confidence: 99%